Anti-adhesive effects of argan oil on postoperative peritoneal adhesions - Oguz Ugur Aydin; Dursun Ozgur Karakas; Batuhan Hazer; Ozgur Dandin; Ibrahim Yilmaz (Medicine Science, 2018)
The aim of this study is to reveal effect of Argan oil on postoperative peritoneal adhesion. Twenty-four Wistar albino rats were divided into three groups. After laparotomy was carried out intraperitoneally, 0,9% NaCl and 3 ml Argan Oil applied to saline and Argan oil groups, respectively. Four subjects in each groups were sacrificed at postoperative day 3 and 7. Macroscopic adhesions and microscopic cellular reactions, such as giant cell, lymphocyte/plasmocyte, neutrophil and histiocyte, were assessed and hydroxyproline levels were measured in all three groups. Adhesion and fibrosis scores were lower both 3rd and 7th days in Argan oil, but only lower fibrosis scores were statistically significant (p [Med-Science 2018; 7(3.000): 557-60]